Fruit - Lieth, Pure (London Hamlyn, 1993)
The "Confident Cooking" series consists of six titles: "Soups and Starters", "Salads", "Vegetarian Cooking", "Quick and Easy", "Fruit", and "Chicken Dishes". Each title contains over 25 fully tested recipes, each with step-by-step instructions and colour photographs.
Including Illustrations and Index
Keywords: Cooking (Fruit) -- Desserts